A Novel Approach to Predict the Growth of Staphylococcus aureus on Rice Cake - Wang, Jun; Koseki, Shige; Chung, Mi-Ja; Oh, Deog-Hwan (Frontiers in Microbiology, 2017)
This study aimed to investigate the growth kinetics of Staphylococcus aureus on rice cake and to determine the shelf life based on the probability model of the increase in S. aureus contamination on rice cake. Secondary models were developed based on the growth parameters derived from the Baranyi model at constant temperatures (15, 25, 35 and 45°C). External validation was then conducted using additional data under experimental conditions not used in development of the models to verify the performance and reliability of the developed model through different goodness-of-fit indices. Furthermore, the growth of S. aureus on rice cake under dynamic temperature was obtained with the RMSE of 0.218 and the 90.9% acceptable prediction rate. In addition, probability models of the 1-log, 2-log, 3-log and 4-log increases of S. aureus on rice cake were also developed from the data, which could provide the probability and the time to a certain log increase. The results of validation demonstrated that the developed predictive model and the obtained growth parameters could be used for evaluating the growth behavior of S. aureus on rice cake under different conditions, and qualified to supply sufficient information for microbiological risk assessment (MRA) studies of S. aureus on rice cake in Korea.